Le travail rémunéré à temps partiel chez les élèves de niveau secondaire - Drapeau, Sylvie; Fournier, Geneviève; Cloutier, Richard (Canadian Journal of Counselling and Psychotherapy, 2007)
This article intends to answer two main questions: 1) who are the young québécois students working part-time? and 2) is there a relationship between part-time work and how these young students function in school? The sample is composed of 5,328 students of secondary levels 1 to V, of which 2,173 work part-time (2,016 work less than 20 hours a week and 157 work 20 hours and more). The results show that there are more students working in the late secondary years. Also, more boys than girls are spending 20 hours and more a week at their jobs. Regarding the relationship between part-time work and school functioning of these students, many significant differences were noticed between working students, particularly the ones spending 20 hours and more a week at work, and the non-working students. Thus, an intensive job is associated with an impression of unease with school, lower academic aspirations, more frequent non-motivated absences, and less time devoted to school work, reading and watching television.